2008
DOI: 10.1016/j.ydbio.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

cis-Regulatory sequences driving the expression of the Hbox12 homeobox-containing gene in the presumptive aboral ectoderm territory of the Paracentrotus lividus sea urchin embryo

Abstract: Embryonic development is coordinated by networks of evolutionary conserved regulatory genes encoding transcription factors and components of cell signalling pathways. In the sea urchin embryo, a number of genes encoding transcription factors display territorial restricted expression. Among these, the zygotic Hbox12 homeobox gene is transiently transcribed in a limited number of cells of the animal-lateral half of the early Paracentrotus lividus embryo, whose descendants will constitute part of the ectoderm ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 85 publications
(90 reference statements)
6
41
0
Order By: Relevance
“…Micro1/pmar1-related genes, PlHbox12, Hpmicro1, Sppmar1, Acmicro1, and Lvpmar1, have been isolated, respectively, from five sea urchins belonging to the order Echinoida: Paracentrotus lividus, Hemicentrotus pulcherrimus, Strongylocentrotus purpuratus, Bernardo et al, 1995;Kitamura et al, 2002;Oliveri et al, 2002;Nishimura et al, 2004;Wu and McClay, 2007). Micro1/pmar1 represents a multicopy gene with polymorphic loci clustered along the Echinoida genome (Nishimura et al, 2004;Sea Urchin Genome Sequencing Consortium, 2006;Ettensohn et al, 2007;Cavalieri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Micro1/pmar1-related genes, PlHbox12, Hpmicro1, Sppmar1, Acmicro1, and Lvpmar1, have been isolated, respectively, from five sea urchins belonging to the order Echinoida: Paracentrotus lividus, Hemicentrotus pulcherrimus, Strongylocentrotus purpuratus, Bernardo et al, 1995;Kitamura et al, 2002;Oliveri et al, 2002;Nishimura et al, 2004;Wu and McClay, 2007). Micro1/pmar1 represents a multicopy gene with polymorphic loci clustered along the Echinoida genome (Nishimura et al, 2004;Sea Urchin Genome Sequencing Consortium, 2006;Ettensohn et al, 2007;Cavalieri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we have shown in P. lividus that the Hbox12 homeodomain repressor is expressed by prospective dorsal ectoderm cells, spatially facing and preceding the onset of nodal transcription, where it acts preventing the ectopic activation of nodal expression [51][52][53][54]. Functional analysis revealed that expression of hbox12 and nodal genes are mutually exclusive and both required for DV polarization.…”
Section: Nodal-expressing Organizing Centrementioning
confidence: 94%
“…Although the spatial distribution of Myb in the early embryo has not yet been determined, Myb is a redox-sensitive factor [59,60] known to act as a repressor in ventral territories of the sea urchin embryo [61]. This evidence has been provided by the cis-regulatory analysis of the CyIIIa and hbox12 genes, both beginning to be specifically transcribed in the presumptive dorsal ectoderm during early embryogenesis [52,61]. Surprisingly, the cis-regulatory apparatus of the nodal gene also contains a Myb-like consensus binding sequence that, when mutated in gene transfer assays, leads to increased reporter expression [39].…”
Section: Nodal-expressing Organizing Centrementioning
confidence: 99%
“…Reverse-transcription and Q-PCR analysis were performed as described previously (Cavalieri et al, 2008;Cavalieri et al, 2009a). The oligonucleotide sequences, length, and amplicon size are described in Table S1 in the supplementary material.…”
Section: Rna Extraction Reverse-transcription Quantitative-pcr and mentioning
confidence: 99%